New Features on the Expression and Trafficking of mGluR1 Splice Variants Exposed by Two Novel Mutant Mouse Lines - Naito, Rika; Kassai, Hidetoshi; Sakai, Yusuke; Schönherr, Sabine; Fukaya, Masahiro; Schwarzer, Christoph; Sakagami, Hiroyuki; Nakao, Kazuki; Aiba, Atsu; Ferraguti, Francesco (Frontiers in Molecular Neuroscience, 2018)
Metabotropic glutamate receptors (mGluRs) couple to G-proteins to modulate slow synaptic transmission via intracellular second messengers. The first cloned mGluR, mGluR1, regulates motor coordination, synaptic plasticity and synapse elimination. mGluR1 undergoes alternative splicing giving rise to four translated variants that differ in their intracellular C-terminal domains. Our current knowledge about mGluR1 relates almost entirely to the long mGluR1 isoform, whereas little is known about the other shorter variants. To study the expression of mGluR1γ, we have generated by means of the CRISPR/Cas9 system a new knock-in mouse line in which the C-terminus of this variant carries two short tags. Using this mouse line, we could establish that mGluR1γ is either untranslated or in amounts that are undetectable in the mouse cerebellum, indicating that only mGluR1 and mGluR1 are present and active at cerebellar synapses. The trafficking and function of mGluR1 appear strongly influenced by adaptor proteins such as long Homers that bind to the C-terminus of mGluR1. We generated a second transgenic mouse line in which mGluR1 carries a point mutation in its Homer binding domain and studied whether disruption of this interaction influenced mGluR1 subcellular localization at cerebellar parallel fiber-Purkinje cell (PC) synapses by means of the freeze-fracture replica immunolabeling technique. These transgenic animals did not show any overt behavioral phenotype, and despite the typical mGluR1 perisynaptic distribution was not significantly changed, we observed a higher probability of intrasynaptic diffusion suggesting that long Homers regulate the lateral mobility of mGluR1. We extended our ultrastructural analysis to other mouse lines in which only one mGluR1 variant was reintroduced in PC of mGluR1-knock out mice. This work revealed that mGluR1 preferentially accumulates closer to the edge of the postsynaptic density, whereas mGluR1 has a less pronounced perijunctional distribution and, in the absence of mGluR1, its trafficking to the plasma membrane is impaired with an accumulation in intracellular organelles. In conclusion, our study sets several firm points on largely disputed matters, namely expression of mGluR1γ and role of the C-terminal domain of mGluR1 splice variants on their perisynaptic clustering.